2003
DOI: 10.1016/s0899-3467(07)60042-1
|View full text |Cite
|
Sign up to set email alerts
|

Spinal manipulation and anterior headweighting for the correction of forward head posture and cervical hypolordosis: A pilot study

Abstract: (J Chiropr Med 2003;2: 51-54)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…This weighting system process has been previously tested and described. 13,14 All patients in this study were prescribed their own sets of this weighting system for both in-office treatment as well as home use. Each patient came to the author's office for a specified treatment period and then was released from care and followed up 1 to 4 times annually, depending upon the length of care, the severity of the primary scoliosis, and the amount of curve correction obtained.…”
Section: Methodsmentioning
confidence: 99%
“…This weighting system process has been previously tested and described. 13,14 All patients in this study were prescribed their own sets of this weighting system for both in-office treatment as well as home use. Each patient came to the author's office for a specified treatment period and then was released from care and followed up 1 to 4 times annually, depending upon the length of care, the severity of the primary scoliosis, and the amount of curve correction obtained.…”
Section: Methodsmentioning
confidence: 99%
“…This device and method have been previously reported (6,7). The patient was instructed to wear this headweight at home twice daily for 20 minutes each time.…”
Section: Methodsmentioning
confidence: 99%
“…Specific techniques have been identified that show reasonable effectiveness at restoring cervical lordosis (3)(4)(5)(6)(7). Unfortunately, there is little evidence to show if any techniques can effectively treat cervical hyperlordosis, or if those techniques designed to correct cervical kyphosis or hypolordosis are contraindicated in instances of cervical hyperlordosis.…”
Section: Introductionmentioning
confidence: 99%
“…I previously outlined this procedure. (6,7) In conjunction with the anterior headweight, the patient also wore a backpack with 25 pounds of weight over the low shoulder. The weight hangs around the patient's waistline, thereby enhancing the lumbar lordosis immediately.…”
Section: Case Reportmentioning
confidence: 99%